An unpopular view on tax monitoring - E. N. Kolesnikova (Вестник университета)
In the article, the author considers a set of problems associated with the unsatisfactory efficiency of tax monitoring as a form of tax control. A critical analysis of the essence, content and results of the implementation of tax monitoring is presented, which is distinguished by a risk-based approach to conducting control procedures, the active use of digital technologies and the information openness of the system participants. The objectives of the study included assessing the results of tax monitoring already achieved and reviewing the practice of implementing similar forms of tax monitoring (observation) abroad. The study revealed the low efficiency of tax monitoring procedures in the system of tax control measures in foreign countries and the lack of relevant data indicating the effectiveness of tax monitoring in Russia. The conclusion about the need for a balanced and prudent approach to the further development of tax monitoring systems is made and the need for an additional study of the tax behavior of business entities is substantiated.